Using Design Fiction to Inform Shape-Changing Interface Design and Use. (28th July 2017) - Sturdee, Miriam; Coulton, Paul; Alexander, Jason
Abstract: Shape-changing interfaces are tangible, physically dynamic devices which enable user-experience beyond 2D screens. Within Human Computer Interaction, researchers are developing these from low-resolution, low-fidelity prototypes, toward a vision of a truly malleable world. The main focus is in producing and testing hardware, and basic user interactions, which leaves the question unanswered: what are shape-changing interfaces good for? In response, we propose the use of design fiction to investigate potential applications for this technology: to create and analyse artifacts relating to future use-scenarios for shape-change. Whilst research within shape-change often proposes future use-cases for prototypes during discussion, they are seldom in a form that presents them as everyday artifacts. Here, we present and discuss a printed game-play instruction manual for a truly high resolution shape-changing game entitled First Hand, which aims to draw parallels between current gaming practices and the tangible nature of shape-changing interfaces.